Fifth IEEE International Conference on Advanced Learning Technologies (ICALT'05) 2005
DOI: 10.1109/icalt.2005.51
|View full text |Cite
|
Sign up to set email alerts
|

An empirical exploration of using Wiki in an English as a second language course

Abstract: In this paper, we present an empirical study of using a new and cost-effective Web-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The use of wikis for English for Academic Purposes (EAP) and English for Special Purposes (ESP) has also been examined by some researchers. Various collaborative writing tasks were implemented in a course of Effective Communication in English (Kuteeva, 2011), in an ESP course for software engineering students (Bradley, Lindström, & Rystedt, 2010;Bradley, Lindström, Rystedt, & Vigmo, 2010), sociology students (Zorko, 2009) and students of accountancy (Alyousef & Picard, 2011) Lin & Yang, 2011), summary or essay writing on the wiki (Bradley, Lindström, & Rystedt, 2010;Elola & Oskoz, 2010;Kost, 2011;Kuteeva, 2011;Turgut, 2009;Wang, Lu, Yang, Hu, Chiou, Chiang, & Hsu, 2005;Wichadee, 2010), writing emails and letters (Kovacic et al, 2008) and report writing (Alyousef & Picard, 2011;Papadima-Sophocleous & Yerou, 2013;Zorko, 2009). Two studies described the production of an online picture book and a children's book on the wiki (Lee & Wang, 2013;Moreno, 2009), while two projects involved writing about culture (Kessler, 2009;Kessler & Bikowski, 2010).…”
Section: Wikis Used For Collaborative Writing In Language Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of wikis for English for Academic Purposes (EAP) and English for Special Purposes (ESP) has also been examined by some researchers. Various collaborative writing tasks were implemented in a course of Effective Communication in English (Kuteeva, 2011), in an ESP course for software engineering students (Bradley, Lindström, & Rystedt, 2010;Bradley, Lindström, Rystedt, & Vigmo, 2010), sociology students (Zorko, 2009) and students of accountancy (Alyousef & Picard, 2011) Lin & Yang, 2011), summary or essay writing on the wiki (Bradley, Lindström, & Rystedt, 2010;Elola & Oskoz, 2010;Kost, 2011;Kuteeva, 2011;Turgut, 2009;Wang, Lu, Yang, Hu, Chiou, Chiang, & Hsu, 2005;Wichadee, 2010), writing emails and letters (Kovacic et al, 2008) and report writing (Alyousef & Picard, 2011;Papadima-Sophocleous & Yerou, 2013;Zorko, 2009). Two studies described the production of an online picture book and a children's book on the wiki (Lee & Wang, 2013;Moreno, 2009), while two projects involved writing about culture (Kessler, 2009;Kessler & Bikowski, 2010).…”
Section: Wikis Used For Collaborative Writing In Language Teachingmentioning
confidence: 99%
“…Bonk et al (2009) discovered that while students accepted an internal critique partner easily, they had reservations about an external one from another institution. Wang et al (2005) investigated the relationship between the frequency of editing and students' performance in the final exam and found that students with low editing usage performed better. Nevertheless, no causality was implied and the need for further research was announced.…”
Section: Wikis Used For Peer Review and Assessmentmentioning
confidence: 99%
“…The use of collaborative WEB environments is now commonplace in university education [1] [2]. The new technology platforms such as Blogs, Wikis and RSS feeds are proving to be invaluable educational tools that satisfy the constructivist theories of active learning [3].…”
Section: Introductionmentioning
confidence: 99%